2016
DOI: 10.1007/s12010-016-2090-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of the Relative Effects of Various Mutations in Major Histocompatibility Complex I—a Way to Predict Protein-Protein Interactions

Abstract: Protein-protein interactions (PPIs) play pivotal roles in most of the biological processes. PPI dysfunctions are therefore associated with disease situations. Mutations often lead to PPI dysfunctions, but there are certain other types of mutations which do not cause any appreciable abnormalities. This second type of mutations is called polymorphic mutations. So far, there are many studies that deal with the identification of PPI sites, but clear-cut analyses of the involvements of mutations in PPI dysfunctions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is reported that the acidic environment after the metabolism of tumours is not conducive to normal cells and results in the immune escape of tumour cells 73 . PPIs can directly change the quantity of T‐cell receptors (TCR) or major histocompatibility complex (MHC) so as to improve the recognition and elimination of tumour cells by T cells 74 . Alkalizing the acidic environment of tumour cells can also improve the activity of other effector cells such as natural killer cells (NK) or natural killer T cells (NKT) 75 .…”
Section: Tumour Microenvironment Is the Main Medium For The Prolifera...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the acidic environment after the metabolism of tumours is not conducive to normal cells and results in the immune escape of tumour cells 73 . PPIs can directly change the quantity of T‐cell receptors (TCR) or major histocompatibility complex (MHC) so as to improve the recognition and elimination of tumour cells by T cells 74 . Alkalizing the acidic environment of tumour cells can also improve the activity of other effector cells such as natural killer cells (NK) or natural killer T cells (NKT) 75 .…”
Section: Tumour Microenvironment Is the Main Medium For The Prolifera...mentioning
confidence: 99%
“… 73 PPIs can directly change the quantity of T‐cell receptors (TCR) or major histocompatibility complex (MHC) so as to improve the recognition and elimination of tumour cells by T cells. 74 Alkalizing the acidic environment of tumour cells can also improve the activity of other effector cells such as natural killer cells (NK) or natural killer T cells (NKT). 75 Under the acidic environment, tumour cells can use the nutrition provided by autophagy of normal cells to meet the needs of tumour cell growth.…”
Section: Tumour Microenvironment Is the Main Medium For The Prolifera...mentioning
confidence: 99%